Efficient channel estimation using TCH codes - Lopes, B. (2017)
In this paper, we consider the use of TCH codes to perform channel estimation in an OFDM system, using either data multiplexed pilots or superimposed pilots over the data. TCH codes possess several properties that allow us to use them efficiently in various applications which includes channel estimation, as we address in this paper. With this objective, several performance results were obtained through simulations which allowed the evaluation of the impact of different pilot power levels and modulations, as well as the comparison of TCH against other conventional pilots. In order to cope with the interference between pilots and data, an iterative receiver with interference suppression was employed for the superimposed pilots method.